Judaizm jako religia uświęcająca czas - ZAJĄC, Ewa (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
Judaism is a religion of history, a religion of time, and one which actually aims at the sanctification of time. Judaism constantly reminds human beings that while living in the natural world, subjected to space and time, as well as to nature’s laws, they simultaneously live in the holy dimension and that one is incapable of abandoning this dimension much as one is incapable of overcoming nature’s laws. Abraham Joshua Heschel used to say that one can break with the holy dimension neither through sin, nor through stupidity, dissent or ignorance. Life ineviatably continues in the proximity of the sacred, endowing existence with the highest meaning. Thus the entire life of a Jew is placed within a net of rites and rituals whose purpose is to sanctify human existence. The ony exception is the Sabbath, which is God’s gift to the human beings. Unlike the spatial world, which provides merely the sense of temporality, the Sabbath offers a taste of eternity. Translated by Dorota Chabrajska